A comparison between the Dutch and American-English digits-in-noise (DIN) tests in normal-hearing listeners. (2nd June 2016) - Smits, Cas; Watson, Charles S.; Kidd, Gary R.; Moore, David R.; Goverts, S. Theo
Abstract: Objective : The Dutch digits-in-noise test (NL DIN) and the American-English version (US DIN) are speech-in-noise tests for diagnostic and clinical usage. The present study investigated differences between NL DIN and US DIN speech reception thresholds (SRTs) for a group of native Dutch-speaking listeners. Design : In experiment 1, a repeated-measures design was used to compare SRTs for the NL DIN and US DIN in steady-state noise and interrupted noise for monaural, diotic, and dichotic listening conditions. In experiment 2, a subset of these conditions with additional speech material (i.e. US DIN triplets without inter-digit coarticulation/prosody) was used. Study sample : Experiment 1 was conducted with 16 normal-hearing Dutch students. Experiment 2 was conducted with nine different students. Results : No significant differences between SRTs measured with the NL DIN and US DIN were found in steady-state noise. In interrupted noise the US DIN SRTs were significantly better in monaural and diotic listening conditions. Experiment 2 demonstrated that these better SRTs cannot be explained by the combined effect of inter-digit coarticulation and prosody in the American-English triplets. Conclusions : The NL DIN and US DIN are highly comparable and valuable tests for measuring auditory speech recognition abilities. These tests promote across-language comparisons of results.